1999
DOI: 10.1038/sj.onc.1202474
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the wild type p73 gene in human bladder cancer

Abstract: p73, a ®rst p53 relative, was recently identi®ed and shown to be monoallelically expressed in a number of dierent human tissues. To determine the potential role of this gene in human bladder cancer, we investigated p73 expression levels, allelic expression patterns, and analysed p73 mutations in 23 unselected primary invasive bladder cancers with matched normal tissues and in seven bladder cancer cell lines. In a comparison between normal and tumor tissues using quantitative RT ± PCR analysis, we found that p7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 19 publications
5
79
1
Order By: Relevance
“…p73 mutations seem to be a very rare event. However, the expression of p73 has been shown to be higher in tumour tissue than in the corresponding normal tissue both at the mRNA level (Loiseau et al, 1999;Takada et al, 1999;Yokomizo et al, 1999) and at the protein level (Bjork-Eriksson et al, 1999;MacCallum and Hupp, 1999;Peters et al, 1999;Scherr, 1999;Tannapfel et al, 1999;Cai et al, 2000;Herath et al, 2000;Ng et al, 2000). The origin of such increased expression and its function in tumorigenesis is not known, but it could be involved in the triggering of this p73 immune response.…”
Section: Discussionmentioning
confidence: 99%
“…p73 mutations seem to be a very rare event. However, the expression of p73 has been shown to be higher in tumour tissue than in the corresponding normal tissue both at the mRNA level (Loiseau et al, 1999;Takada et al, 1999;Yokomizo et al, 1999) and at the protein level (Bjork-Eriksson et al, 1999;MacCallum and Hupp, 1999;Peters et al, 1999;Scherr, 1999;Tannapfel et al, 1999;Cai et al, 2000;Herath et al, 2000;Ng et al, 2000). The origin of such increased expression and its function in tumorigenesis is not known, but it could be involved in the triggering of this p73 immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Here we observed elevated protein expression and uncharacteristic localization of pinin protein within cells comprising a RCC tumor mass. Although it is generally assumed that tumor suppressors are negative regulators of tumor formation and are often down-regulated in cancer development, observations of over-expression of TS proteins such as pRb, p53, p73, p27, p16 in di erent tumors are not uncommon Doki et al, 1997;Kaur et al, 1998;Shapiro et al, 1995;Warneford et al, 1991;Yokomizo et al, 1999). The over-expression of a tumor suppressor may imply a compensatory mechanism which may function to circumvent the disrupted regulatory pathway of wild-type TS protein (Benedict et al, 1999;Emig et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, also in analogy to other hematological malignancies, rare deletions of p53 as well as p73 seem to be associated with advanced disease stages in MM. Since some studies have indicated that aberrant p73 gene expression levels might play a role in tumor growth or progression, 55 mutational as well as expression analyses of the p73 gene in MM samples are under way to elucidate a possible role of gene silencing and mutation in the pathogenesis of MM.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Mutations or deletions of genes encoding these proteins have rarely been found in human cancers or hematological malignancies so far. 8,[13][14][15][16][17][18][19][20][21] After being mapped to the chromosomal region 1p35-1p36, p73 has been postulated to act as a tumor suppressor gene, as this region was shown to be deleted in several human malignancies including neuroblastoma, pheochromocytoma, oligodendroglioma, melanoma, merkel cell cancer, germ cell cancer, breast cancer, ovarian cancer, liver cancer and colon cancer as well as in some precancerous lesions like colorectal adenomas. 20,[22][23][24][25][26] Recently published preliminary data discussed the role of p73 in hematologic neoplasias, 27,28 as well as in renal cell carcinoma 29 and lung cancer.…”
Section: Introductionmentioning
confidence: 99%